Macrophage Cytophilic Antibody in Mice: Effect of Bacterial Lipopolysaccharide on the Uptake of Immunoglobulins by Mouse Peritoneal Cells - Tizard, Ian R. (1971)
Injection of lipopolysaccharide from Escherichia coli intravenously into mice affected the ability of their peritoneal macrophages to adsorb antisheep erythrocyte cytophilic antibodies in vitro. After a single intravenous injection of lipopolysaccharide, the alteration in antibody uptake took the form of a triphasic response. An early evanescent increase in adsorptive capacity took place, which reached a maximum 5 min after injection and was followed immediately by a phase of depressed uptake of antibody. Enhancement of antibody uptake then increased to reach a maximum about 24 hr after injection, before declining slowly. The second enhancement phase was inhibited by prior immunization with E. coli or after multiple injections of lipopolysaccharide. Exposure of macrophages to lipopolysaccharide in vitro did not alter their capacity to take up cytophilic antibody. Changes in the capacity of macrophages and polymorphonuclear neutrophil leukocytes to adsorb opsonized erythrocytes were induced by injection of lipopolysaccharide and were similar to those induced with respect to the uptake of cytophilic antibodies by macrophages.